Sarcopenia: prevalence and associated factors among elderly from a Brazilian capital - Andreia Pelegrini; Giovana Zaperllon Mazo; André de Araújo Pinto; Tânia Rosane Bertoldo Benedetti; Diego Augusto Santos Silva; Edio Luiz Petroski (Editora Champagnat, 2018)
Abstract Introduction: Sarcopenia has been currently considered a public health problem, affecting a large portion of the elderly and making them more susceptible to the risk of falls. Objective: To estimate the prevalence and factors associated with sarcopenia in the elderly from a Brazilian capital. Methods: This is an epidemiological study with cross-sectional design involving data of 439 elderly people from Florianópolis city, Santa Catarina state. The factors potentially associated with sarcopenia (sex, age, weight status) were tested using binary logistic regression, estimating the Odds Ratio and the respective confidence intervals. Results: The prevalence of sarcopenia was 33.3% (95% CI: 28.9, 36.9). Older women (75 years or more) showed less muscle mass in relation to other age groups (p < 0.05). Elderly men, individuals that are 75 years or more, and those with low weight were the subgroups at higher risk for sarcopenia. Obese individuals were less likely to have the outcome. Conclusion: More than one-third of elderly people were diagnosed with sarcopenia. Men, individuals who are older, and those with low weight had a higher risk of having sarcopenia.